A new species of Bambusaspis Cockerell (Hemiptera: Sternorrhyncha: Coccomorpha) colonising bamboo in Malaysia - Łagowska, Bozena; Martin, Jon H.; Hodgson, Chris J. (Zootaxa, 2015)
All life stages (adult female and male, first-instar nymph, second-instar male and female nymphs, and prepupa and pupa) of a new species of Asterolecaniidae, Bambusaspis transversa Lagowska & Martin sp. n., from bamboo in Malaysia, are described and illustrated. The adult female and first-instar nymphs are compared with those Bambusaspis species considered to be closest to the new species.